Technology Integration in Language Learning to Improve Learning Outcomes - Jatmiko Juhairi; Viktor Siumarlata; Adeena Yaqoob (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The integration of technology in language learning has become a critical strategy to enhance students’ learning outcomes in the digital era. This study aims to examine how technological tools influence learner motivation, engagement, and overall language proficiency. Employing a qualitative descriptive approach through a systematic literature review, this research analyzes 30 scholarly works published between 2023 and 2025. The findings reveal that technology integration significantly improves language learning outcomes by promoting interactive learning environments, providing real-time feedback, and facilitating personalized learning experiences. Furthermore, tools such as mobile applications, virtual classrooms, and artificial intelligence contribute to increased student motivation and autonomy. However, challenges such as digital literacy gaps and unequal access remain significant barriers. The study concludes that effective implementation of technology requires strategic pedagogical planning and institutional support. This research contributes to the development of technology-enhanced language learning frameworks and offers recommendations for educators and policymakers.